The effect of haptens on protein‐carrier immunogenicity. Issue 1 (January 2015) - Gefen, Tal; Vaya, Jacob; Khatib, Soliman; Rapoport, Irena; Lupo, Meital; Barnea, Eilon; Admon, Arie; Heller, Elimelech Dan; Aizenshtein, Elina; Pitcovski, Jacob
Summary The immune response against hapten is T‐cell‐dependent, and so requires the uptake, processing and presentation of peptides on MHC class II molecules by antigen‐presenting cells to the specific T cell. Some haptens, following conjugation to the available free amines on the surface of the carrier protein, can reduce its immunogenicity. The purpose of this study was to explore the mechanism by which this occurs. Four proteins were tested as carriers and six molecules were used as haptens. The immune response to the carrier proteins was reduced > 100‐fold by some of the haptens (termed carrier immunogenicity reducing haptens – CIRH), whereas other haptens did not influence the protein immunogenicity (carrier immunogenicity non‐reducing haptens – nCIRH). Conjugation of the protein to a CIRH affected protein degradation by lysosomal cathepsins, leading to the generation of peptides that differ in length and sequence from those derived from the same native protein or that protein modified with nCIRH. Injection of CIRH‐conjugated protein into mice induced an increase in the population of regulatory T cells. The results of this study provide a putative mechanism of action for the reduction of immune response to haptenated proteins.